2003
DOI: 10.1161/01.hyp.0000046280.16849.bf
|View full text |Cite
|
Sign up to set email alerts
|

Two Loci Affect Angiotensin I–Converting Enzyme Activity in Baboons

Abstract: Abstract-Serum LDL cholesterol (LDLC) concentrations and ACE activities are risk factors for the development of cardiovascular disease (CVD). However, the relationship between ACE and CVD susceptibility, and possible mechanisms of action, is controversial. With data on 622 pedigreed baboons, we used statistical genetic methods to determine the mode of inheritance of ACE activities and its relationship to LDLC on different diets. ACE activity was moderately heritable, and quantitative trait linkage analyses det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
9
2
Order By: Relevance
“…4 The within-run and between-run coefficients of variation for this assay were 1.4% and 4.6%, respectively. ACE activities were transformed by natural logarithms before analysis to reduce skewness.…”
Section: Phenotypes and Genotypesmentioning
confidence: 80%
See 1 more Smart Citation
“…4 The within-run and between-run coefficients of variation for this assay were 1.4% and 4.6%, respectively. ACE activities were transformed by natural logarithms before analysis to reduce skewness.…”
Section: Phenotypes and Genotypesmentioning
confidence: 80%
“…In addition, a genome scan of ACE activities in baboons did not reveal any QTLs for ACE activities on the baboon homologue of human chromosome 4q. 4 Several genome screens for QTLs influencing blood pressure have been performed in mice and rats, but a search of the mouse genome with the NCBI Map Viewer (http://www.ncbi.nlm.nih.gov/mapview/) revealed no blood pressure QTLs on mouse chromosomes 3 or 8, the regions that are homologous to human chromosome 4q (http:// www.ncbi.nlm.nih.gov/Homology/). In contrast, use of the Virtual Comparative Map tool from the Rat Genome Database revealed several blood pressure QTLs on rat chromosomes 2q, 16p12-14, and 19p12-q12, the regions that exhibit homology to human chromosome 4q (http://rgd.mcw.edu/ VCMAP/).…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge about the genetic architecture underlying variation in baboon serum ACE activity suggests gene-specific similarities to humans. In particular, interindividual variation in circulating ACE has been demonstrated to have a heritable component in baboons attributable in part to a locus on baboon chromosome 17 near the baboon homologue of the human ACE gene (Kammerer et al, 2003). This evidence suggests that a segregating variant in the baboon ACE gene may associate with variation in baboon ACE activity in a manner similar to that observed in humans.…”
mentioning
confidence: 89%
“…ACE polymorphism Kammerer et al (2003) identified a major quantitative trait locus (QTL) for variation in baboon ACE protein activity located near the baboon ACE homologue on chromosome 17. This result is consistent with a number of studies that have identified functionally important variation in nonhuman primates at or near sites homologous to known functional variants in humans (Trefilov et al, 2000;Newman et al, 2005;Loisel et al, 2006;Wooding et al, 2006).…”
Section: Identification Of a Baboon-specificmentioning
confidence: 99%
See 1 more Smart Citation